Respiratory Physiology of Prone Positioning With and Without Inhaled Nitric Oxide Across the Coronavirus Disease 2019 Acute Respiratory Distress Syndrome Severity Spectrum. (15th June 2021) - Ziehr, David R.; Alladina, Jehan; Wolf, Molly E.; Brait, Kelsey L.; Malhotra, Atul; La Vita, Carolyn; Berra, Lorenzo; Hibbert, Kathryn A.; Hardin, C. Corey
Abstract : Supplemental Digital Content is available in the text. Abstract : IMPORTANCE: Prone positioning improves clinical outcomes in moderate-to-severe acute respiratory distress syndrome and has been widely adopted for the treatment of patients with acute respiratory distress syndrome due to coronavirus disease 2019. Little is known about the effects of prone positioning among patients with less severe acute respiratory distress syndrome, obesity, or those treated with pulmonary vasodilators. OBJECTIVES: We characterize the change in oxygenation, respiratory system compliance, and dead-space-to-tidal-volume ratio in response to prone positioning in patients with coronavirus disease 2019 acute respiratory distress syndrome with a range of severities. A subset analysis of patients treated with inhaled nitric oxide and subsequent prone positioning explored the influence of pulmonary vasodilation on the physiology of prone positioning. DESIGN, SETTING, AND PARTICIPANTS: Retrospective cohort study of all consecutively admitted adult patients with acute respiratory distress syndrome due to coronavirus disease 2019 treated with mechanical ventilation and prone positioning in the ICUs of an academic hospital between March 11, 2020, and May 1, 2020. MAIN OUTCOMES AND MEASURES: Respiratory system mechanics and gas exchange during the first episode of prone positioning. RESULTS: Among 122 patients, median (interquartile range) age was 60 years (51–71 yr), median body mass index was 31.5 kg/m 2 (27–35 kg/m 2 ), and 50 patients (41%) were female. The ratio of Pao 2 to Fio 2 improved with prone positioning in 90% of patients. Prone positioning was associated with a significant increase in the ratio of Pao 2 to Fio 2 (from median 149 [123–170] to 226 [169–268], p < 0.001) but no change in dead-space-to-tidal-volume ratio or respiratory system compliance. Supine ratio of Pao 2 to Fio 2, respiratory system compliance, positive end-expiratory pressure, and body mass index did not correlate with absolute change in the ratio of Pao 2 to Fio 2 with prone positioning. However, patients with ratio of Pao 2 to Fio 2 less than 150 experienced a greater relative improvement in oxygenation with prone positioning than patients with ratio of Pao 2 to Fio 2 greater than or equal to 150 (median percent change in ratio of Pao 2 to Fio 2 62 [29–107] vs 30 [10–70], p = 0.002). Among 12 patients, inhaled nitric oxide prior to prone positioning was associated with a significant increase in the ratio of Pao 2 to Fio 2 (from median 136 [77–168] to 170 [138–213], p = 0.003) and decrease in dead-space-to-tidal-volume ratio (0.54 [0.49–0.58] to 0.46 [0.44–0.53], p = 0.001). Subsequent prone positioning in this subgroup further improved the ratio of Pao 2 to Fio 2 (from 145 [122–183] to 205 [150–232], p = 0.017) but did not change dead-space-to-tidal-volume ratio. CONCLUSIONS AND RELEVANCE: Prone positioning improves oxygenation across the acute respiratory distress syndrome severity spectrum, irrespective of supine respiratory system compliance, positive end-expiratory pressure, or body mass index. There was a greater relative benefit among patients with more severe disease. Prone positioning confers an additive benefit in oxygenation among patients treated with inhaled nitric oxide.